Penerapan Metode ATC/DDD dalam Analisis Penggunaan Antibiotik Pasien Rawat Inap di RSUD Chasan Boesoirie Ternate - Muhammad Subhan A. Sibadu; Siti Marita Umaternate; Ismail Rahman (Universitas Muhammadiyah Prof. DR. HAMKA, 2025)
The irrational use of antibiotics has the potential to increase the risk of bacterial resistance. Quantitative approaches, such as the Defined Daily Dose (DDD) method, can be utilised to evaluate the types and volumes of antibiotics consumed. The purpose of this study was to analyse the use of antibiotics at Dr H. Chasan Boesoirie (RSCB) Ternate Hospital in 2024 using the DDD approach. The research employed an observational approach using medical record data from RSCB, with a population of 1,300 during 2024. The inclusion criteria were inpatients diagnosed with bacterial infections, receiving antibiotic therapy, having clear and complete medical record data, aged over 18 years up to 65 years, and with a discharge status of “permitted” or “improved.” Study showed that the most widely used antibiotics were ceftriaxone, with a value of 45.7 DDD/100 patient-days of care, and ciprofloxacin 0.5 DDD/100 patient-days of care. The total DDD of all antibiotics was 61.7 DDD/100 patient-days of care. The 90% Drug Use (DU) segment was ceftriaxone with a value of 73.6, and the highest 10% DU was metronidazole at 9%. In conclusion, the antibiotic with the highest DDD value was ceftriaxone (45.7 DDD/100 patient-days), while the lowest was ciprofloxacin (0.1 DDD/100 patient-days).